2015
DOI: 10.1016/j.freeradbiomed.2015.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin scavenges chloramines and inhibits myeloperoxidase-induced protein/lipid oxidation in physiologically relevant hyperbilirubinemic serum

Abstract: Hypochlorous acid (HOCl), an oxidant produced by myeloperoxidase (MPO), induces protein and lipid oxidation, which is implicated in the pathogenesis of atherosclerosis. Individuals with mildly elevated bilirubin concentrations (i.e. Gilbert's syndrome; GS) are protected from atherosclerosis, cardiovascular disease (CVD) and related-mortality. We aimed to investigate Albumin-bound UCB efficiently and specifically (3.9-125 µM; P<0.05) scavenged taurine-, glycine-and N-α-acetyl-lysine-chloramines. These results w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 65 publications
(91 reference statements)
3
31
0
Order By: Relevance
“…Relative reductions in MDA and protein carbonyl content were similar (~30–40%), suggesting relatively broad antioxidant specificity of UCB. Bilirubin protects against lipid and protein oxidation in serum of GS individuals, supporting a conclusion that bilirubin protects from tissue injury via an antioxidant mechanism of action . The impact of bilirubin's effect is highlighted by the profound reduction in infarct size reported here, a cardio‐protective effect that correlates favourably with tissue bilirubin content.…”
Section: Discussionsupporting
confidence: 78%
“…Relative reductions in MDA and protein carbonyl content were similar (~30–40%), suggesting relatively broad antioxidant specificity of UCB. Bilirubin protects against lipid and protein oxidation in serum of GS individuals, supporting a conclusion that bilirubin protects from tissue injury via an antioxidant mechanism of action . The impact of bilirubin's effect is highlighted by the profound reduction in infarct size reported here, a cardio‐protective effect that correlates favourably with tissue bilirubin content.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have shown that the uraemic state is associated with low concentrations of GSH and reduced thiols (SH), which continue to decrease with the progression of kidney failure in dialysis patients 45 . Our findings, therefore, may indicate that bilirubin plays an important role in maintaining circulating thiol status providing an important pool of antioxidant capacity, which can protect proteins and lipids from oxidation by oxidants produced during inflammation, namely hypochlorous acid produced from myeloperoxidase (MPO) 46 . The importance of MPO-catalysed protein and lipid adduct formation has been considered an important mechanistic link between oxidation, atherosclerosis and kidney disease 47 , which bilirubin effectively inhibits 46 .…”
Section: Discussionmentioning
confidence: 91%
“…Hypochlorous acid (HOCl), an oxidant produced by myeloperoxidase (MPO), can induce protein and lipid oxidation. An in vitro experimental study showed that the addition of exogenous UCB to the serum and plasma of humans and rats can protect proteins and lipids from MPO-induced oxidation and reduce the production of chloramine and its decomposition products induced by HOCl and MPO [33].…”
Section: Discussionmentioning
confidence: 99%